The value of chemical shift magnetic resonance imaging in characterization of bone tumors - Mohammed Mohsen Emam; Amr Farouk Ibrahim; Heba Ahmed Kamal Ali; Wessam Gamal Eldin Abosenna (Cairo : Mohammed Mohsen Emam, 2020)
Purpose: To evaluate the signal characteristics of opposed phase imaging and signal intensity ratio in benign and malignant bone tumors and tumor like lesions aiming at the possible differentiation of such entities by setting an optimal cut-off value.Material and Methods: Between July 2019 and March 2020 49 patients diagnosed with 14 bone tumors and tumor like conditions (10 benign and 4 malignant) were assessed by conventional and chemical shift MR imaging. Chemical shift imaging was carried out by axial in-phase (repetition time (TR), 500 ms; echo time (TE), 4.6 ms; flip angle, 80{u00B0}) and opposed-phase (TR, 500 ms, TE, 4.6ms, flip angle, 80{u00B0}). Areas that elicited pathological signal intensity on the T1 and T2 sequences were identified on the in-phase/opposed-phase sequences. a region of interest was made on the abnormal areas to measure their signal intensity on the in-phase as well as on the opposed-phase images. Signal intensity ratio (SIR) was calculatedby dividing the opposed-phase signal intensity on the in-phase signal intensity.Results: 49 lesions were included (29 benign and 20 malignant).There was a significant difference (P < 0.001, independent t test) in the mean SIR for the benign lesions (mean, 0.59; SD, 0.28) compared with the malignant lesions (mean, 0.99; SD, 0.08). ROC analysis yielded optimal cut off values at > 0.93 correctly diagnosing 19 out of 20 malignant lesions and 25 out of 29 benign lesions(sensitivity, 94.7%; specificity, 86.6%), area under the curve (AUC, 0.888), (positive predictive value, 81.8%), (negative predictive value, 96.3%) and (95% confidence interval, 0.765 - 0.960)
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Radio-Diagnosis
Issued also as CD
Keywords: BoneTumors; Chemical shift imaging (CSI); Magnetic resonance imaging (MRI)